2011
DOI: 10.1007/s10682-011-9525-3
|View full text |Cite
|
Sign up to set email alerts
|

Costs of inflorescence longevity for an Asian fig tree and its pollinator

Abstract: In ecological situations where interactions between two species are to their mutual benefit, traits are expected to evolve to maximise the value of the timing of their encounters. Plants that depend on animals for pollination vary in the longevity of their flowers and also in how the quality of the rewards they offer varies in flowers of different ages. However, costs of floral longevity are rarely studied. Using field experiments with Ficus semicordata, a SE Asian dioecious fig tree, we examined sexual differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…Younger female figs are typically more successful at setting good quality seed, so overlap between the start of female receptivity and pollinator release will be most favorable for the plants [26], [51]. However, in Taohua island, there are both early and late flowering females coinciding with the emergence of both pollinators.…”
Section: Discussionmentioning
confidence: 99%
“…Younger female figs are typically more successful at setting good quality seed, so overlap between the start of female receptivity and pollinator release will be most favorable for the plants [26], [51]. However, in Taohua island, there are both early and late flowering females coinciding with the emergence of both pollinators.…”
Section: Discussionmentioning
confidence: 99%
“…Figs start to become less attractive to other pollinators a few hours after they have been entered, though this is postponed in some species if they have only received a single pollinator [20,21]. The cessation of release of attractant volatiles may reflect both the termination of production and closure of the ostiole.…”
Section: Introductionmentioning
confidence: 99%
“…Floral longevity (the length of time that a flower remains available for pollination) varies greatly among different plant species, and reflects a balance between the benefits of greater likelihood of pollinator visitation and the cost of flower maintenance [2225]. Figs display extended floral longevity and if they are not entered by fig wasps they remain attractive to pollinators for days or weeks [20,21,26], but prolongation of receptivity may come at the cost of reduced reproductive efficiency among older figs [20]. Two studies have reported that pollinator females are more likely to enter younger figs [21,26], though the proximal causes of this preference have not been established.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations